Estudo comparativo entre diferentes processamentos histológicos na interpretação de biopsias testiculares - Augusto Barbosa Reis (2012)
To better understand the pathological processes that affect the azoospermic man's testicle, the present study aimed to compare methods of fixation of testicular biopsies. To do so, testicular biopsies were collected from 21 azoospermic men, and cut into three fragments. The first was processed by the conventional technique (Bouin /paraffin) while the second was processed by the method of fixation in glutaraldehyde and embedded in a plastic resin-based glycol methacrylate (GMA) and the third used to search for the presence of sperm. The histopathological changes were described comparatively considering three different scores: (i) five patterns (most commonly usedin pathology), (ii) Johnsen and (iii) Bergmann. In addition, clinical data were collected such as testicular volume, blood samples for serum total testosterone and follicle stimulating hormone analysis. All parameters were evaluated based on cytological differences and chances of finding sperm in the testicular biopsies. The results showed that both techniques were similar in the grades evaluation of the three different types of scores used. However some individuals (21%) showed an improvement in the histopathological diagnosis when evaluated with the technique of fixation in glutaraldehyde and embedding in GMA. The patterns which showed the biggest changes were from hypospermatogenesis to normal spermatogenesis and fromtesticular atrophy or sclerosis to maturation arrest. This improvement in the patients scores is related to an increased chance of finding sperm in a new testicular biopsy. Moreover, the glutaraldehyde / GMA, technique showed a higher correlation between the three scores - five patterns, Johnsen and Bergmann - and the presence of spermatozoa. Among the scores, Bergmann showed the best correlation with increased chance of finding sperm in five individuals (26%) out of the 19 evaluated. Concerning the clinical data, testicular volume and hormonal measurements were similar between the groups with or without the presence of sperm in testicular biopsies. In conclusion, the present study demonstrated that testicular biopsies preparation with the glutaraldehyde / GMA technique is more accurate in the diagnosis of certain azoospermia pathologies and improves the chance of azoospermic patients, which could have been considered incapable by the traditional method, to become biological parents.